2014
DOI: 10.1016/j.carj.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal Solid Organ Injuries: An Enhanced Management Algorithm

Abstract: The organ injury scale grading system proposed by the American Association for the Surgery of Trauma provides guidelines for operative versus nonoperative management in solid organ injuries; however, major shortcomings of the American Association for the Surgery of Trauma injury scale may become apparent with low-grade injuries, in which conservative management may fail. Nonoperative management of common intra-abdominal solid organ injuries relies increasingly on computed tomographic findings and other clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
2
10
0
4
Order By: Relevance
“…However, both MRCP and ERCP have higher sensitivity (approaching 100%) and each have their own indications when pancreatic injury and ductal disruption is suspected. 37,38,46 MRCP has the advantage of being non-invasive and is the first choice in a stable patient with suspicion of a pancreatic injury and to diagnose any injury to the pancreatic duct. Intraparenchymal hematoma may cause duct compression (showing as loss of duct on imaging).…”
Section: Diagnostic Modalities and Investigationmentioning
confidence: 99%
“…However, both MRCP and ERCP have higher sensitivity (approaching 100%) and each have their own indications when pancreatic injury and ductal disruption is suspected. 37,38,46 MRCP has the advantage of being non-invasive and is the first choice in a stable patient with suspicion of a pancreatic injury and to diagnose any injury to the pancreatic duct. Intraparenchymal hematoma may cause duct compression (showing as loss of duct on imaging).…”
Section: Diagnostic Modalities and Investigationmentioning
confidence: 99%
“…Currently the indications for splenectomy in ASR, regardless of known or unknown etiology, have generally included those identified in association with splenic rupture owing to blunt abdominal trauma: hemodynamic instability, high grade splenic injury, and signs of peritonitis. 8 Renzulli et al performed a comprehensive review of ASR in the literature and similarly found the paucity of patient data as well as the simple rarity of ASR limiting to their analyses. 4 They were able however to find an overall ASR-related mortality rate of 12.2%, as well as to make several conclusions relating to risk factors and management of ASR as a general entity.…”
Section: Discussionmentioning
confidence: 99%
“…Spesifik, direkt bulgular, pankreasta boyut artışı, laserasyon (fokal lineer kontrast tutmayan alan), inhomojen kontrast tutulumu, fragmantasyon ve hematom olarak görülebilir. İndirekt, nonspesifik bulgular, peripankreatik yağ planlarında silinme, laserasyonla ilişkili peripankreatik sıvı, splenik ven ve pankreas arasında sıvı, hemoraji, sol anterior pararenal fasiyada kalınlaşma, komşu yapılarda eşlik eden yaralanmalar olarak sayılabilir [1,4,[18][19][20][21][22].…”
Section: Pankreas Yaralanmalarıunclassified
“…Laserasyonlar, yüzeyel (parankim kalınlığının <%50 den azı) ve derin laserasyon(parankim kalınlığının >%50'den fazlası) olarak sınıflanır (Şekil 4, 5 [22][23][24][25].…”
Section: Pankreas Yaralanmalarıunclassified
See 1 more Smart Citation